Relation Maxim Flouting as an Avoidance Strategy Signaling Geralt's Moral Stance in "The Lesser Evil" - Farrel Maulana Azhani; Almira Irwaniyanti Utami (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
Conversational indirectness in literary dialogue often reveals more about a character than their explicit statements. This study examines how the flouting of the maxim of relation functions as a conversational avoidance strategy in Geralt's dialogue in "The Lesser Evil," a short story from The Witcher: The Last Wish by Andrzej Sapkowski, and how this strategy contributes to the construction of his moral character. Using a qualitative approach with purposive sampling, eleven utterances were selected from Geralt's dialogues with Renfri, Stregobor, and Caldemeyn based on their departure from conversational relevance, their function as avoidance, and their occurrence in morally complex situations. The data were analyzed using Grice's Cooperative Principle and Gushchina and Nikolaeva's avoidance strategy categories. The findings show that Geralt flouts the maxim of relation through topic shifting, indirect refusal, sarcasm, humor, and philosophical generalization, with each interlocutor eliciting a distinct avoidance pattern. These strategies generate implicatures that allow him to resist direct moral commitment while still implying a position. The study demonstrates that relation maxim flouting can function as a cumulative, discourse-level resource for character construction, extending Grice's utterance-level framework toward a broader application in pragmatic stylistics.